2022
DOI: 10.1038/s41598-021-04627-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Pseudomonas aeruginosa cell surface via GP12, an Escherichia coli specific bacteriophage protein

Abstract: Bacteriophages are highly abundant molecular machines that have evolved proteins to target the surface of host bacterial cells. Given the ubiquity of lipopolysaccharides (LPS) on the outer membrane of Gram-negative bacteria, we reasoned that targeting proteins from bacteriophages could be leveraged to target the surface of Gram-negative pathogens for biotechnological applications. To this end, a short tail fiber (GP12) from the T4 bacteriophage, which infects Escherichia coli (E. coli), was isolated and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Xanthine was identified as a potential biomarker and its rapid detection may strongly reduce the time between the onset of symptoms and administration of suitable antimicrobials, which should help avoiding high mortality rates [ 54 ]. Moreover, based on the high level and preferential binding of the receptor binding protein GP12, from T4 bacteriophages to the LPS structures on the surface of P. aeruginosa cells, this protein has been proposed for P. aeruginosa detection in future diagnostic and therapeutic applications [ 55 ]. On its side, the Enc34 endolysin from bacteriophage Enc34, containing an N-terminal enzymatically active endolysin domain and a C-terminal transmembrane domain, displays a peptidoglycan-degrading activity towards outer membrane-permeabilized P. aeruginosa PAO1 [ 56 ].…”
Section: Main Textmentioning
confidence: 99%
“…Xanthine was identified as a potential biomarker and its rapid detection may strongly reduce the time between the onset of symptoms and administration of suitable antimicrobials, which should help avoiding high mortality rates [ 54 ]. Moreover, based on the high level and preferential binding of the receptor binding protein GP12, from T4 bacteriophages to the LPS structures on the surface of P. aeruginosa cells, this protein has been proposed for P. aeruginosa detection in future diagnostic and therapeutic applications [ 55 ]. On its side, the Enc34 endolysin from bacteriophage Enc34, containing an N-terminal enzymatically active endolysin domain and a C-terminal transmembrane domain, displays a peptidoglycan-degrading activity towards outer membrane-permeabilized P. aeruginosa PAO1 [ 56 ].…”
Section: Main Textmentioning
confidence: 99%
“…RBPs with lower specificity such as the Gp12, described by Ongwae et al [59], that recognized both E. coli and P. aeruginosa. This strategy would contribute to decreasing the total assay cost and capturing different bacterial species with the same probe, thus not compromising the bead surface area availability.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Conversely, other phage-based microfluidic systems that were tested in blood are not fully integrated, such as the study reported by Dow et al [39]. Phage proteins, in particular, receptor binding proteins (RBPs) have been proven as valuable recognition elements in a variety of bacterial detection systems [57][58][59] due to their outstanding specificity, stability, and feasibility for the detection of numerous pathogens in different types of samples [58,60]. In biosensing systems, phage proteins can be more reliable due to their small size reducing distances between probe and analyte, which is important in some sensors whose sensitivity depends upon the distance to the analyte [61,62].…”
Section: Introductionmentioning
confidence: 99%